Translating Good Governance into Patient Satisfaction: The Mediating Role of Service Quality in Indonesian Primary Healthcare - Putu Essa Kana Putri; Ida Bagus Teddy Prianthara (Al-Qalam Institute, 2026)
Patient satisfaction is a critical indicator of public healthcare performance, particularly in primary healthcare facilities where patients directly experience governance practices through service procedures, communication, waiting time, and complaint handling. This study examines how good governance influences patient satisfaction through service quality in Indonesian primary healthcare. The study was conducted at Puskesmas IV Denpasar Selatan using a quantitative explanatory design. Data were collected through structured questionnaires distributed to 370 patients selected using proportional random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0. The results show that good governance has a positive and significant effect on service quality (β = 0.785, t = 26.484, p < 0.001) and patient satisfaction (β = 0.174, t = 3.168, p = 0.002). Service quality also has a positive and significant effect on patient satisfaction (β = 0.684, t = 13.610, p < 0.001). Furthermore, service quality partially mediates the relationship between good governance and patient satisfaction (β = 0.537, t = 11.485, p < 0.001). These findings indicate that governance practices contribute more strongly to patient satisfaction when translated into better service structures, processes, and outcomes. Theoretically, this study advances public administration and healthcare management literature by integrating Governance Theory, Donabedian's healthcare quality model, and the SERVQUAL framework into a single empirical model. Practically, primary healthcare facilities should strengthen transparency, accountability, queue management, complaint handling, and empathetic communication to improve patient satisfaction.